2021
DOI: 10.1136/bmjopen-2020-045127
|View full text |Cite
|
Sign up to set email alerts
|

Levels of burn-out among healthcare workers during the COVID-19 pandemic and their associated factors: a cross-sectional study in a tertiary hospital of a highly burdened area of north-east Italy

Abstract: ObjectiveTo determine burn-out levels and associated factors among healthcare personnel working in a tertiary hospital of a highly burdened area of north-east Italy during the COVID-19 pandemic.DesignObservational study conducted from 21 April to 6 May 2020 using a web-based questionnaire.SettingResearch conducted in the Verona University Hospital (Veneto, Italy).ParticipantsOut of 2195 eligible participants, 1961 healthcare workers with the full range of professional profiles (89.3%) completed the survey.Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
184
11
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(270 citation statements)
references
References 41 publications
23
184
11
19
Order By: Relevance
“…According to Alsulimani LK et al, the prevalence of burnout among HCWs in Saudi Arabia, which has one of the best healthcare systems in the Middle East (AlHumaid et al, 2020),was 75% during the COVID-19 pandemic (Alsulimani et al, 2021). In Europe, Italy was severely impacted by COVID-19, and Italian HCWs reported relevant work-related burnout symptoms (Barello et al, 2020;Lasalvia et al, 2021). According to MD Trani, 56% of HCWs in Italy showed EE Abbreviations: COVID-19, Novel coronavirus disease; HCW, Healthcare worker; MBI scale, Maslach Burnout Inventory scale; EE, emotional exhaustion; DP, depersonalization; PA, personal accomplishment; PPE, personal protective equipment; CR, composite reliability; AVE, average variance extracted.…”
Section: Introductionmentioning
confidence: 99%
“…According to Alsulimani LK et al, the prevalence of burnout among HCWs in Saudi Arabia, which has one of the best healthcare systems in the Middle East (AlHumaid et al, 2020),was 75% during the COVID-19 pandemic (Alsulimani et al, 2021). In Europe, Italy was severely impacted by COVID-19, and Italian HCWs reported relevant work-related burnout symptoms (Barello et al, 2020;Lasalvia et al, 2021). According to MD Trani, 56% of HCWs in Italy showed EE Abbreviations: COVID-19, Novel coronavirus disease; HCW, Healthcare worker; MBI scale, Maslach Burnout Inventory scale; EE, emotional exhaustion; DP, depersonalization; PA, personal accomplishment; PPE, personal protective equipment; CR, composite reliability; AVE, average variance extracted.…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review, female physicians were at higher risk of burnout most likely due to difficulties in balancing between work demands and family responsibilities 22 . This situation also was seen among healthcare provider in Italy and Japan 23,24 The race was not significantly associated with personal-related and work-related burnout, but interestingly, after further analysis of clientrelated burnout among the races, it was reported that Sabah and Sarawak Bumiputera doctors were noted to be three times more likely to experience client-related burnout compared to the Chinese doctors. The Sabah and Sarawak Bumiputera doctors were minority groups in this medical field, hence, they had difficulties in coping with the working environment and the high expectations from patients 25 .…”
Section: Resultsmentioning
confidence: 76%
“…Limited resources, longer hours, sleep, work-life balance disturbances, and occupational hazards associated with COVID-19 exposure have led to adverse psychological outcomes among healthcare employees regarding post-traumatic stress, insomnia, anxiety, and depression. 16,17 Healthcare workers, like everyone else, are vulnerable both to the disease itself and to rumors and incorrect information that necessarily increases their anxiety levels. Healthcare workers' anxiety was further impacted by growing stigmatization and loss of trust in their communities.…”
Section: Discussionmentioning
confidence: 99%